Pengaruh Pemberian Sinbiotik dari Kulit Nanas dan Inulin Bengkuang pada Pakan Komersial terhadap Giblet Dan Lemak Abdomen Ayam Broiler: The Effect of Synbiotics from Pineapple Peel and Jicama Inulin in Commercial Feed on Giblet and Abdominal Fat of Broiler Chickens - Almadani, Hanif; Rinawidiastuti, Rinawidiastuti; Zulfanita, Zulfanita (Universitas Muhammadiyah Purworejo, 2025)
This study aimed to determine the effect of synbiotic supplementation from pineapple skin and jicama inulin in commercial feed on giblet weight and abdominal fat in broiler chickens. The research involved 100 broiler chickens raised for 35 days. A Completely Randomized Design (CRD) was used with 5 treatments and 4 replications. The treatments consisted of adding synbiotic flour to commercial feed at different levels: P1 (0%), P2 (5%), P3 (10%), P4 (15%), and P5 (20%). The observed parameters included the weight percentage and volume of giblets (liver, heart, gizzard), the percentage of abdominal fat, and liver color. Data were analyzed using ANOVA and followed by Duncan's New Multiple Range Test (DMRT) at a 5% significance level. The results showed that synbiotic supplementation had no significant effect (P>0.05) on the weight percentage and volume of giblets. However, the treatment addition of synbiotics from pineapple skin and inulin from bengkuang had a highly significant effect (P<0.05) on the percentage of abdominal fat, which increased with higher levels of synbiotic supplementation, from 0.48% (P1) to 2.07% (P5). Visual observation also indicated signs of hepatic lipidosis in several samples. It was concluded that the addition of up to 20% synbiotics is safe for giblet organs but significantly increases abdominal fat deposition, which is presumably caused by the high energy content of the tapioca flour used as a binder in the synbiotic preparation